1923
DOI: 10.1098/rstb.1923.0008
|View full text |Cite
|
Sign up to set email alerts
|

VIII.—Observations upon the effect of high altitude on the physiological processes of the human body, carried out in the Peruvian Andes, chiefly at Carro de Pasco. - Report to the Peru High-Altitude Committee

Abstract: What is reported in the following pages is an example of work achieved in a relatively short time by the co-operation of a sufficient number of institutions and individuals. The venue of this research was in the Andes, and the work was carried out in the winter 1921-1922, yet its organisation only commenced definitely in the early summer of 1921, when a group of British and American physiologists secured the support of the various universities or other institutions to which they were attached. This support was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
2
2

Year Published

1937
1937
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(42 citation statements)
references
References 12 publications
0
38
2
2
Order By: Relevance
“…He suggested that at lower altitudes there is the presence of some other acid, due to an acid-base adjustment performed by the kidneys. In yet another study Barcroft et al (1923) reported a left-shifted ODC at altitude as measured at the prevailing PCO 2 , which in this particular study was between 25-30 mmHg. This leftward shift was attributed to alkalemia and was argued to be beneficial, as it would enhance O 2 loading at the lung.…”
Section: The Odc In Lowlanders At High Altitudementioning
confidence: 96%
See 2 more Smart Citations
“…He suggested that at lower altitudes there is the presence of some other acid, due to an acid-base adjustment performed by the kidneys. In yet another study Barcroft et al (1923) reported a left-shifted ODC at altitude as measured at the prevailing PCO 2 , which in this particular study was between 25-30 mmHg. This leftward shift was attributed to alkalemia and was argued to be beneficial, as it would enhance O 2 loading at the lung.…”
Section: The Odc In Lowlanders At High Altitudementioning
confidence: 96%
“…The ODC was first measured in highlanders at altitude by Barcroft et al (1923), who reported a left-shifted curve in Peruvian highlanders as compared to that of lowlanders at sea level. This was attributed to alkalemia of acclimatization, since a similar shift was observed in the lowlanders studied at the same altitude.…”
Section: The Odc In Highlandersmentioning
confidence: 99%
See 1 more Smart Citation
“…The subject of cellular hypoxia became a focus of metabolic research already at the beginning of the 20th century. First blood gas analyses were reported as early as 1919 [16], and in 1923 it was observed in studies at high altitudes that in thin air, study subjects would involuntarily lose weight [44]. Evidence for reduced tissue oxygen supply came mostly from indirect observations like increased erythropoietic activity and elevated lactate production.…”
Section: Pioneering Studiesmentioning
confidence: 99%
“…The most commonly held theory, for which there is considerable support, implies that one of the factors which controls red blood cell production is the oxygen tension in the marrow itself. Since chronic hypoxia is associated with secondary polycythemia (2,43,44), it is assumed that the resultant low oxygen tension in marrow stimulates erythrocytogenesis. Conversely, if erythroid tissue is exposed to an increased oxygen tension, the rate of red cell formation would be expected to decrease.…”
Section: Discussionmentioning
confidence: 99%